Seasonal patterns of urban bird diversity in a Mediterranean coastal city: the positive role of open green spaces - Tzortzakaki, Olga; Kati, Vassiliki; Kassara, Christina; Tietze, Dieter Thomas; Giokas, Sinos (Urban ecosystems, 2018)
Urbanization causes rapid changes in the landscape and land use, exerting a significant pressure on bird communities. The effect of urbanization on bird diversity has been widely investigated in many cities worldwide; however, our knowledge on urban bird communities from the eastern Mediterranean region is very scarce. In this context, we aimed to investigate the effect of the different land-cover types on bird species richness and abundance in a densely built coastal Mediterranean city (Patras, Greece) during the breeding and wintering seasons. We sampled the bird community in 90 randomly selected sites along an urbanization gradient. Open green spaces proved to be the most significant factor favouring bird diversity in both seasons. In winter, woody vegetation and impervious surfaces had a positive effect on species richness as well. The local bird community consisted of a large number of species associated with open and semi-open unmanaged green areas, 12 of which are Species of European Conservation Concern (SPECs) showing a declining trend in Europe. On the other hand, in winter the number of forest-dwellers increased significantly. Species richness was significantly higher in winter indicating that the urban environment provides important wintering grounds. Thus, management actions in cities with similar characteristics in the Mediterranean region should focus on the maintenance of open green spaces and woody vegetation patches to enhance bird diversity.
Gesehen am 13.02.2018